Synthesis, Characterization and Biological Evaluation of NovelMacrocyclic Metal ‎Complexes: Insights from Spectroscopic Analysis, Molecular Docking, Antioxidant Studies‎, andAntimicrobial Screening - Gulia , Rajrani; Sindhu , Indu; Singh , Anshul; Patel , Neetu (International Journal of Advanced Chemistry, 2025)
Significant contributions to the development of inorganic chemistry were made by macrocyclic complexes. It has stimulated interest in the study of macrocyclic metal ‎complexes in the design and development of novel antibiotics. In this regard, a series of nine ‎novel macrocyclic complexes of Co(II), Ni(II), and Cu(II) were synthesized by a template approach ‎in a [2:1:2] ratio utilizing o-phenylenediamine and dicarboxylic acid. The newly designed ‎complex's structure has been verified by elemental analysis, Fourier transform infrared, UV-Visible, mass spectrometry, thermogravimetric (TG) analysis, and EPR studies. The Coats-Redfern method was employed for the evaluation of various thermodynamic parameters. Based on ‎the spectral studies distorted octahedral geometry has been proposed around the central metal ion ‎in the synthesized complexes. The synthesized complexes were evaluated against Gram-positive ‎bacteria [S. aureus, B. subtilis] and Gram-negative [E. coli, P. aeruginosa] along with fungal ‎strains [C. albicans and A. niger] to assist their antimicrobial potential by agar well diffusion ‎method. Furthermore, the complexes have also been examined for their antioxidant activity ‎utilizing the DPPH assay. Subsequently, molecular docking studies were performed using the Auto ‎Dock Vina programme to assess the biological significance of the synthesized complexes and ‎determine effective binding modes between different ligands and the receptor proteins. The ‎copper macrocyclic complexes demonstrated excellent biocidal action against the selected ‎microbes. Copper acetate exhibited the highest antioxidant potential. The obtained results revealed ‎that the synthesized macrocyclic complexes are potent for making them attractive metal-based ‎antimicrobial and antioxidant prototypes‎.